2016
DOI: 10.1002/car.2448
|View full text |Cite
|
Sign up to set email alerts
|

The Buffering Effect of Parental Mediation in the Relationship between Adolescents' Cyberbullying Victimisation and Adjustment Difficulties

Abstract: As cyberbullying research advances, many researchers have focused on identifying factors that might reduce the negative consequences associated with cyberbullying victimisation. One prominent factor receiving attention is the role of parental mediation in digital technology use, and how such mediation reduces the risk of cybervictimisation. Parents utilise different mediation strategies (i.e. restrictive, co‐viewing, instructive), which could potentially contribute to differential patterns in the relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
(60 reference statements)
0
19
0
5
Order By: Relevance
“…In this study, parental monitoring of online accounts was included as restrictive mediation, which does not qualify as restrictive (Livingstone & Helsper, 2008). Conversely, Wright (2016) found that restrictive mediation increased cyber victimization, arguing that restrictive mediation was not enough to prevent victimization. Sometimes, children are afraid to tell their parent about being cyberbullied because they do not want more restrictions (Navarro et al, 2013).…”
Section: Restrictive Mediation and Cyberbullyingmentioning
confidence: 75%
See 1 more Smart Citation
“…In this study, parental monitoring of online accounts was included as restrictive mediation, which does not qualify as restrictive (Livingstone & Helsper, 2008). Conversely, Wright (2016) found that restrictive mediation increased cyber victimization, arguing that restrictive mediation was not enough to prevent victimization. Sometimes, children are afraid to tell their parent about being cyberbullied because they do not want more restrictions (Navarro et al, 2013).…”
Section: Restrictive Mediation and Cyberbullyingmentioning
confidence: 75%
“…There have been several studies that have examined the implementation of online rules in relation to children's negative online experiences (e.g., Chang et al, 2015;Spears et al, 2005;Wright, 2016), however, research has yielded mixed findings. Spears and colleagues (2005) found that restrictive mediation reduced negative online activities such as visiting inappropriate sites, meeting strangers, and revealing personal information.…”
Section: Restrictive Mediation and Cyberbullyingmentioning
confidence: 99%
“…Cyberbullying significantly affects children’ and adolescents’ social, emotional, and academic well-being. Different studies have shown that victims of cyberbullying are more likely than non-victimized youths to report emotional distress, depression symptoms, low self-esteem, anxiety, social isolation, less life satisfaction, school absenteeism, poor academic performance, and suicidal ideation [ 19 , 20 , 21 , 22 ]. Cyberbullying perpetration is also associated with anxiety, depression, low life satisfaction, loneliness and poor academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The next paper, by Michelle Wright (), segues usefully with the previous one in that it presents research on one of the four categories of intervention identified by Wurtele and Kenny; namely, ‘parental mediation’ – in this instance, regarding ‘cyberbullying’. Wright's work is also useful in that it acts as a reminder that while online sexual victimisation tends to receive much more attention in the media, CYP are considerably more at risk of cyberbullying.…”
mentioning
confidence: 99%
“…The threats from digital technology‐based harms and the responses with which they have been met have been shown to be multidimensional, with many of these individual ‘dimensions’ having discrete child protection implications. For example, the capacity of a digital technology‐based interaction to cause harm to a child may be dependent upon his or her particular circumstances (Greenhow et al ., ); the efficacy of an intervention may vary according to the specific form that it takes (Wright, ); and difficulties in managing child protection concerns may heighten when communicating digitally (Lamberton et al , ).…”
mentioning
confidence: 99%